Typing of Echinococcus multilocularis by Region-Specific Extraction and Next-Generation Sequencing of the mitogenome - Rachel, Franziska; Luttermann, Christine; Höper, Dirk; Conraths, Franz Josef; Dapprich, Johannes; Maksimov, Pavlo (Frontiers in Microbiology, 2025)
BackgroundInfection by the fox tapeworm Echinococcus multilocularis may lead to a severe zoonosis in humans, alveolar echinococcosis, which may be fatal if left untreated. Typing is important to understand the epidemiology of this parasite, yet there is limited knowledge on the microdiversity of E. multilocularis on the local scale, since the typing resolution of established methods is restricted.MethodsThe mitogenome of E. multilocularis was used as the target regions to modify, apply and validate the Region-Specific Extraction (RSE) method in combination with Next-Generation Sequencing (NGS). Single Nucleotide Polymorphisms (SNPs) were detected in the mitochondrial DNA (mtDNA) and analysed bioinformatically. To validate the success and the accuracy of the RSE protocol, the mitogenomes of some E. multilocularis isolates were also analysed by the Whole-Genome Sequencing (WGS).ResultsWith the chosen combination of methods, the entire mitogenome (~13 kb) of E. multilocularis could be captured and amplified. The read depth (median ≥ 156X) was sufficient to detect existing SNPs. The comparison of mitogenome sequences extracted by RSE with mitogenome sequences obtained by WGS showed that the accuracy of the RSE method was consistently comparable to direct Whole-Genome Sequencing.ConclusionThe results demonstrate that the RSE method in combination with NGS is suitable to analyse the microdiversity of E. multilocularis at the whole mitogenome level. For the capture and sequencing of large (several kb) genomic regions of E. multilocularis and other applications, this method can be very helpful.